Investigation Study towards Housing Attributes Effect House Buyers - Sbakhi, Bissan; Shafiei, Mohd Wira Mohd; Esa, Muneera (International Journal of Engineering and Technology, 2018)
A house is considered the main priority for all people. It is not only a place that saves individuals from dangers but it is a place that all can find themselves in and personal behavior can create. The house is the place that all actions happen and all the social relationships are improved. Moreover, a house shows different cultures and social networks because people culture and thought are developed in the house. It has a strong importance for individuals; so, it is necessary for households to have the comfortable house for living. It is important to define the characteristics of house buyers in order to improve the customer's requirements. In order to understand the process of consumer housing purchase choice, it is important to understand the meaning of housing attributes in details and survey the previous literature related to houses purchasing.